2018
DOI: 10.1021/acs.orglett.8b03537
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Cyclopropanoids via Substrate-Based Cyclization Pathways

Abstract: A series of unexpected reactions triggered by the dimethyloxosulfonium methylide led to the discovery of unconventional approaches for the synthesis of cyclopropafused tetralones and indeno-spirocyclopropanes. These highly functionalized structures were further elaborated in one step to privileged scaffolds such as tetralones, indenones, and fluorenones. As a whole, the results presented herein establish new diversity-oriented folding pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 81 publications
2
11
0
Order By: Relevance
“…To establish a desymmetrizing event facilitated by the DOSM, we have chosen 1 a as the model substrate, Scheme . It is anticipated that the reaction of 1 a with DOSM can involve an initial Michael addition followed by either an aldol‐type reaction (path‐a) or a Michael reaction (path‐b) leading to the formation of zwitterionic species A or B , respectively . A subsequent 1,3‐proton shift provides enolates C or D , which can form indanone 2 a or fused‐cycloheptanedione 3 a , respectively, via the nucleophilic displacement of the dimethylsulfoxonium group.…”
Section: Figuresupporting
confidence: 91%
See 2 more Smart Citations
“…To establish a desymmetrizing event facilitated by the DOSM, we have chosen 1 a as the model substrate, Scheme . It is anticipated that the reaction of 1 a with DOSM can involve an initial Michael addition followed by either an aldol‐type reaction (path‐a) or a Michael reaction (path‐b) leading to the formation of zwitterionic species A or B , respectively . A subsequent 1,3‐proton shift provides enolates C or D , which can form indanone 2 a or fused‐cycloheptanedione 3 a , respectively, via the nucleophilic displacement of the dimethylsulfoxonium group.…”
Section: Figuresupporting
confidence: 91%
“…2019, 14,4568 -4571 www.chemasianj.org cyclization of vinyl-cyclopropyl cationic system [13] generates tetrahydrofluorenyl cation H,w hichu ndergoes deprotonation followed by aromatization to provide the fluorenone 8a.I ntrigued by the unexpected outcomea nd having realized the significance of fluorenones, [9,14] we verified the generalityo f the reactioni nf ew other cases (8b-8f). Asian J.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…For the synthesis of diverse indanone-containing polycyclic compounds, 1,3-indanediones are useful candidates because they have three contiguous electrophilic and nucleophilic reactive sites in the cyclic 1,3-dicarbonyl scaffold. More interestingly, the base- or acid-catalyzed self-condensation of 1,3-indanedione afforded the reactive dimer of 1,3-indanedione (bindone) and the cyclotrimer of 1,3-indanedione (truxenone) as well as other oligomers according to the reaction conditions . Both bindone and truxenone are useful scaffolds for various polymer materials such as nonlinear optical, organic photovoltaics, and semiconductors. , On the other hand, the facile base-catalyzed Knoevenagel condensation of 1,3-indanedione with aromatic aldehydes afforded more reactive dipolarophilic 2-arylidene-1,3-indanediones, which were widely employed in many Michael addition, Diels–Alder, annulation, and versatile transformation reactions. Recently, we successfully found that the triethylamine-promoted reaction of 1,3-indanedione with 3-arylideneindolin-2-ones in ethanol gave carbamato-substituted indeno­[1,2- a ]­fluorenes, in which the bindone was in situ generated and underwent a further domino reaction process .…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the nature of the EWG in E , synthesis of a variety of indenones and fluorenones ( F – H ) with unusual substitution patterns is achieved under thermal conditions. Thereby, a new substrate-based diversity-oriented folding pathway is also established …”
mentioning
confidence: 95%